Implementation of Federal Research Projects as a Tool to Enhance the Training Quality of Master's Program; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Larionov K. B. Kirill Borisovich; Lavrinenko S. V. Sergey Viktorovich; Gubin V. E. Vladimir Evgenievich; Kitaev A. Artem (2015, 2015)
Title screen